2008
DOI: 10.1038/sj.mp.4002150
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin as a natural antipsychotic: a study using oxytocin knockout mice

Abstract: It has been previously suggested that oxytocin (Oxt) may act as a natural antipsychotic. To test this hypothesis, we investigated whether disruption of the oxytocin gene (OxtÀ/À) made mice more susceptible to the psychosis-related effects of amphetamine (Amp), apomorphine (Apo) and phencyclidine (PCP). We examined drug-induced changes in the prepulse inhibition (PPI) of the startle reflex, a measure of sensorimotor gating deficits characteristic of several psychiatric and neurological disorders, including schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 81 publications
3
65
1
2
Order By: Relevance
“…It is possible that reduction in PPI at the luteal phase is not fully explained by changes in estrogen and also includes the influence of hormones, such as oxytocin. Oxytocin varies across the menstrual cycle in non-pill user healthy young women (lower during the luteal phase compared with the follicular and ovulatory phases; eg, Salonia et al, 2005), and shown recently to have influence in PPI, via glutamatergic component, in experimental animals (Caldwell et al, 2009). This study may also be limited by relatively smaller fluctuations in estrogen, relative to progesterone.…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 99%
“…It is possible that reduction in PPI at the luteal phase is not fully explained by changes in estrogen and also includes the influence of hormones, such as oxytocin. Oxytocin varies across the menstrual cycle in non-pill user healthy young women (lower during the luteal phase compared with the follicular and ovulatory phases; eg, Salonia et al, 2005), and shown recently to have influence in PPI, via glutamatergic component, in experimental animals (Caldwell et al, 2009). This study may also be limited by relatively smaller fluctuations in estrogen, relative to progesterone.…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 99%
“…Vasotocin and isotocin are the fish homologues of vasopressin and oxytocin, two nonapeptides closely associated with sociality in mammals (including affiliative and sexual behaviours [32]), plus social/ emotional processing, stress response modulation, learning and memory [33][34][35][36]. Oxytocin has antipsychotic properties [28,37,38] and has been shown to restore deficits in sensorimotor gating induced by MK-801 in rats [39]. The association between MK-801 exposure and isotocin/vasotocin may indicate an unexpected conservation with mammalian patterns in modulating aspects of glutamatergic signalling in fish, and may also reflect molecular stress and coping responses to cognitive disruption [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin receptor knockout mice had normal acoustic startle (Lee et al, 2008). Oxytocin also did not affect pre-pulse inhibition of startle (PPI) by itself (Feifel and Reza, 1999), but disruption of PPI by phencyclidine was enhanced in oxytocin null mice (Caldwell et al, 2009), and oxytocin and a receptor agonist, WAY-267464, reversed the disruption in PPI induced by amphetamine and MK-801 in rats (Feifel and Reza, 1999;Ring et al, 2010). Highly emotional rats that have low plasma levels of oxytocin have increased startle (Uvniis- Moberg et al, 1999).…”
Section: mentioning
confidence: 99%
“…High doses of oxytocin had no effect on startle (Feifel and Reza, 1999), but lower doses increased startle when tested in the dark phase of the day (King et a/, 1985 ). Oxytocin null mice displayed low (Winslow et al, 2000) or normal (Caldwell et al, 2009) startle amplitudes. Oxytocin receptor knockout mice had normal acoustic startle (Lee et al, 2008).…”
Section: mentioning
confidence: 99%